Behaviour of derivatives of the spline-interpolation error - Korneichuk , N. P. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
Assertions are proved clarifying the character of the behavior of the derivatives of the error of interpolation of differentiable periodic functions by splines with respect to the corresponding derivatives of the standard perfect spline determining the error on the entire class of functions.